DNA Mismatch Repair-Induced Double-Strand Breaks - Nowosielska, Anetta (2007)
Escherichia coli dam mutants are sensitized to the cytotoxic action of base analogs, cisplatin and N-methyl-N’-nitro-N-nitrosoguanidine (MNNG), while their mismatch repair (MMR)-deficient derivatives are tolerant to these agents. We showed previously, using pulse field gel electrophoresis, that MMR-mediated double-strand breaks (DSBs) are produced by cisplatin in dam recB (Ts) cells at the non-permissive temperature. We demonstrate here that the majority of these DSBs require DNA replication for their formation, consistent with a model in which replication forks collapse at nicks or gaps formed during MMR. DSBs were also detected in dam recB(Ts) ada ogt cells exposed to MNNG in a dose- and MMR-dependent manner. In contrast to cisplatin, the formation of these DSBs was not affected by DNA replication and it is proposed that two separate mechanisms result in DSB formation. Replication-independent DSBs arise from overlapping base excision and MMR repair tracts on complementary strands and constitute the majority of detectable DSBs in dam recB(Ts) ada ogt cells exposed to MNNG. Replication-dependent DSBs result from replication fork collapse at O(6)-meG base pairs undergoing MMR futile cycling and are more likely to contribute to cytotoxicity. This model is consistent with the observation that fast-growing dam recB (Ts) ada ogt cells, which have more chromosome replication origins, are more sensitive to the cytotoxic effect of MNNG than the same cells growing slowly.